High-durability sealant for sealing steel structure slab joints
By using high-durability sealant composed of modified polysiloxane and other materials in steel structure bridges, the problem of insufficient corrosion resistance of steel plate gaps in humid environments has been solved, and efficient bonding and anti-corrosion effects on the steel plate surface have been achieved, extending the improve the service life of the steel structure.
Patent Information
- Application Number
- CN202411543508.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to effectively realize efficient and long-lasting sealing of steel plate gaps in steel structure bridges, especially inadequate corrosion resistance in humid environments.
A high-durability sealant for seam sealing of steel structures is used. The sealant is composed of modified polysiloxane, silane oligomer, inorganic filler, thixotropic agent, catalyst, cross-linking agent, silane coupling agent, light-stabilized It is composed of agents and antioxidants. Through the charge transfer or coordination between the side chains of modified polysiloxane and Fe atoms on the surface of the steel plate, an adsorption film is formed to block the corrosive medium.
The sealant has good bonding performance on the surface of the steel plate, effectively improves the corrosion resistance of the steel plate, extends the service life of the steel structure, and ensures the safety and long-term stability of the steel structure.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sealing materials, and in particular relates to a high-durability sealant for sealing steel structure plate seams. Background Art
[0002] Large and medium span bridges are the throat of transportation, and their safe operation is directly related to the development of the national economy and social security. Among the many structural forms of railway bridges, steel structure bridges have the advantages of high strength, simple processing, convenient installation, short construction period, good bridge toughness and earthquake resistance compared to concrete bridges, and are widely used in large and medium span bridges. Sealant, as a commonly used caulking sealing material, has good adhesion and durability and can be used to seal steel plate joints in steel structure bridges. Since ordinary steel has poor corrosion resistance and is affected by various factors such as temperature, humidity, ultraviolet rays, and atmospheric environment, the surface of the steel plate is often prone to rust and corrosion to varying degrees. How to efficiently and permanently seal the gaps in the steel plate is of great significance to the overall safety and durability of the steel structure bridge.
[0003] According to the chemical composition, the sealants available on the market can be divided into silicone sealants, polyurethane sealants, acrylate sealants, etc. Among them, silicone sealants are mainly composed of silicone polymers and a series of additives. Patent CN117801782A discloses a silicone sealant and a preparation method thereof. By adopting a modified resin containing a large amount of benzoxazine and benzene ring structure on the molecular chain, the aging resistance of the silicone sealant is increased. By introducing a modified filler containing cage-type silsesquioxane and a metal organic framework staggered structure, the brittleness of the sealant is reduced and the mechanical properties are improved. Patent CN114621724A discloses a two-component silicone sealant, which uses modified oxime-based polydimethylsiloxane in conjunction with other formula components. Compared with the polyalkoxy-terminated polydimethylsiloxane in the prior art, it has higher reaction activity and faster deep curing rate, which improves the curing speed of the sealant. Patent CN116445127A discloses an underwater curable silicone sealant and its preparation method and application. Dopamine and the terminal amino group of bis-aminopropyl-terminated polydimethylsiloxane undergo Michael addition and Schiff base reaction to achieve room temperature crosslinking and curing. Moreover, the reaction can occur underwater (or in a wet environment) to achieve underwater crosslinking and curing. At the same time, because dopamine contains a catechol structure, it can achieve high adhesion on the surface of various materials.
[0004] From the above description, it can be seen that the currently studied organic silicon sealants have certain practical value. According to different formulas and uses, different types of organic groups can be introduced to give organic silicon sealants certain special properties. In view of the more complex and harsh environmental conditions in the current railway bridge projects, mature steel structure plate seam sealant products have not yet been formed. Therefore, providing a steel structure plate seam sealant that has good bonding properties on the steel plate surface and can extend the corrosion resistance of the steel plate in a humid environment has become a technical problem that needs to be solved urgently by those skilled in the art. . Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a plate seam sealing material for steel structure, as well as a preparation method and application of the sealing material.
[0006] The high-durability sealant for sealing steel structure plate seams described in the present invention is characterized in that the sealant comprises the following components in parts by mass: 30 to 50 parts of modified polysiloxane, 1 to 6 parts of silane oligomer, 30 to 60 parts of inorganic filler, 0.1 to 1 part of thixotropic agent, 0.01 to 0.2 part of catalyst, 30 to 60 parts of cross-linking agent, 0.3 to 2 parts of silane coupling agent, 0.1 to 0.5 parts of light stabilizer, and 0.1 to 1 part of antioxidant.
[0007] The modified polysiloxane has the following general formula:
[0008] In the formula, R is any one of methyl, ethyl, n-propyl, and isopropyl.
[0009] 10≤m≤100, 20≤n≤100, m and n are both positive numbers.
[0010] The preparation method of the modified polysiloxane comprises the following steps: The side aminopropyl polysiloxane and the corresponding mass of furfural are dissolved in tetrahydrofuran (THF), the molar ratio of amino group to aldehyde group is controlled at 1:1, anhydrous sodium sulfate (Na2SO4) is added, and the mixture is stirred at room temperature for 24 hours, the Na2SO4 is removed by centrifugation, the solvent is removed by rotary evaporation, and the modified polysiloxane is obtained by vacuum drying in an oven for 12 hours.
[0011] The number average molecular weight of the modified polysiloxane is 6000-20000.
[0012] The inorganic filler includes at least one of calcium carbonate and silicon powder. Further, the calcium carbonate is preferably at least one of heavy calcium carbonate and nano calcium carbonate.
[0013] The catalyst is composed of one or more of dioctyltin diacetate, dioctyltin dilaurate, dioctyltin dioctoate, dibutyltin diacetate, dibutyltin dilaurate, dibutyltin dioctoate, isopropyl titanate, isobutyl titanate, and n-butyl titanate; the crosslinking agent is composed of one or more of methyltriacetoxysilane, ethyltriacetoxysilane, vinyltriacetoxysilane, tetraethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, or vinyltriethoxysilane.
[0014] The light stabilizer is composed of one or more compounds such as benzotriazole ultraviolet light absorbers and hindered amine ultraviolet light stabilizers.
[0015] The silane coupling agent is composed of one or more of 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane or N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane.
[0016] The sealant has good bonding performance on the surface of slightly corroded steel plates, and the bonding strength on the steel surface can reach 3MPa or above.
[0017] The positive effects of the plate seam sealant for steel structure of the present invention are: High-performance sealant is used to seal the joints of steel plates. The N atoms on the side chains of the sealant and the O atoms contain lone pairs of electrons, which can transfer charge or form coordination with the 3d empty orbitals of the Fe atoms on the surface of the steel plate, thereby adsorbing to the surface of the steel plate to form an adsorption film, effectively blocking the entry of corrosive media and playing a corrosion inhibition role. While ensuring the bonding ability, it effectively improves the corrosion resistance of the steel plate, thereby ensuring the safety and long-term stability of the steel structure. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below with reference to the embodiments. Example 1
[0019] A plate seam sealant for steel structure. The preparation steps include: (1) Preparation of modified polysiloxane The aminopropyl polysiloxane and the corresponding mass of furfural are dissolved in THF, the molar ratio of amino group to aldehyde group is controlled at 1:1, Na2SO4 is added, the mixture is stirred at room temperature for 24 hours, the Na2SO4 is removed by centrifugation, the solvent is removed by rotary evaporation, and the modified polysiloxane is obtained by vacuum drying in an oven for 12 hours. The modified polysiloxane has the following structure:
[0020] Wherein, R is methyl; m=100, n=50.
[0021] (2) Preparation of plate seam sealant for steel structure 50 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of heavy calcium carbonate, 0.5 parts of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant were stirred at high speed in vacuum at 120°C for 1 hour; cooled naturally to room temperature, 0.05 parts of catalyst, 30 parts of methyltriethoxysilane and 0.5 parts of 3-aminopropyltrimethoxysilane were added, and high-speed stirring was continued for 20 minutes. After stirring evenly, vacuum treatment was carried out and filling was performed to obtain plate joint sealant for steel structure. Example 2
[0022] The preparation method of this embodiment is basically the same as that of embodiment 1, except for the selection of raw materials and the weight fraction of each raw material, as shown below.
[0023] The modified polysiloxane used in this embodiment has the following structure:
[0024] Wherein, R is methyl; m=10, n=50.
[0025] This embodiment uses 30 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of silicon powder, 0.5 parts of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the cross-linking agent is 30 parts of methyltriacetoxysilane; the silane coupling agent is 1 part of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane. Example 3
[0026] The preparation method of this embodiment is basically the same as that of embodiment 1, except for the selection of raw materials and the weight fraction of each raw material, as shown below.
[0027] The modified polysiloxane used in this embodiment has the following structure:
[0028] Wherein, R is ethyl; m=20, n=100.
[0029] This embodiment uses 30 parts of modified polysiloxane, 3 parts of silane oligomer, 40 parts of silicon powder, 0.5 parts of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the cross-linking agent is 30 parts of methyltriacetoxysilane; the silane coupling agent is 0.5 parts of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane. Example 4
[0030] The preparation method of this embodiment is basically the same as that of embodiment 1, except for the selection of raw materials and the weight fraction of each raw material, as shown below.
[0031] The modified polysiloxane used in this embodiment has the following structure:
[0032] Wherein, R is n-propyl; m=100, n=20.
[0033] This embodiment uses 50 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of calcium carbonate, 1 part of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the cross-linking agent is 40 parts of methyltriacetoxysilane; the silane coupling agent is 2 parts of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane.
[0034] Comparative Example 1: The preparation method of this comparative example is basically the same as that of Example 1, except for the selection of raw materials and the mass fraction of each raw material, as shown below.
[0035] The modified polysiloxane used in this comparative example has the following structure:
[0036] Wherein, R is methyl; m=200, n=50.
[0037] This comparative example uses 50 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of heavy calcium carbonate, 0.5 parts of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the crosslinking agent is 30 parts of methyltriethoxysilane; the silane coupling agent is 0.5 parts of 3-aminopropyltrimethoxysilane.
[0038] Comparative Example 2: The preparation method of this comparative example is basically the same as that of Example 1, except for the selection of raw materials and the mass fraction of each raw material, as shown below.
[0039] The modified polysiloxane used in this comparative example has the following structure:
[0040] Wherein, R is methyl; m=100, n=10.
[0041] This comparative example uses 50 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of heavy calcium carbonate, 0.5 parts of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the crosslinking agent is 30 parts of methyltriethoxysilane; the silane coupling agent is 0.5 parts of 3-aminopropyltrimethoxysilane.
[0042] Comparative Example 3: The preparation method of this comparative example is basically the same as that of Example 1, except for the selection of raw materials and the mass fraction of each raw material, as shown below.
[0043] The modified polysiloxane used in this comparative example has the following structure:
[0044] Wherein, R is methyl; m=10, n=50.
[0045] This comparative example uses 30 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of silicon powder, 0.5 parts of thixotropic agent, 30 parts of methyltriacetoxysilane as the crosslinking agent, and 1 part of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane as the silane coupling agent.
[0046] Comparative Example 4: The preparation method of this comparative example is basically the same as that of Example 1, except for the selection of raw materials and the mass fraction of each raw material, as shown below.
[0047] The modified polysiloxane used in this comparative example has the following structure:
[0048] Wherein, R is methyl; m=200, n=200.
[0049] This comparative example uses 30 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of silicon powder, 0.5 parts of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the cross-linking agent is 30 parts of methyltriacetoxysilane; the silane coupling agent is 1 part of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane.
[0050] Comparative Example 5: The preparation method of this comparative example is basically the same as that of Example 1, except for the selection of raw materials and the mass fraction of each raw material, as shown below.
[0051] The modified polysiloxane used in this comparative example has the following structure:
[0052] Wherein, R is ethyl; m=20, n=0.
[0053] This comparative example uses 30 parts of modified polysiloxane, 3 parts of silane oligomer, 40 parts of silicon powder, 0.5 parts of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the cross-linking agent is 30 parts of methyltriacetoxysilane; the silane coupling agent is 0.5 parts of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane.
[0054] Comparative Example 6: The preparation method of this comparative example is basically the same as that of Example 1, except for the selection of raw materials and the mass fraction of each raw material, as shown below.
[0055] The modified polysiloxane used in this comparative example has the following structure:
[0056] Wherein, R is octadecyl; m=100, n=20.
[0057] This comparative example uses 50 parts of modified polysiloxane, 3 parts of silane oligomer, 30 parts of calcium carbonate, 1 part of thixotropic agent, 0.1 parts of hindered amine UV stabilizer and 0.1 parts of antioxidant, the cross-linking agent is 40 parts of methyltriacetoxysilane; the silane coupling agent is 2 parts of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane.
[0058] The sealing colloids of each embodiment and comparative example were evenly applied to the steel surface to form tensile bonding samples. After curing for 28 days under standard conditions, the initial tensile bonding and elongation at break tests were performed in accordance with the standard GBT 13477.8-2017 "Test methods for building sealing materials Part 8: Determination of tensile bonding", and the tensile bonding and elongation at break tests were performed on the specimens after UV aging for 720 hours and wet heat aging for 720 hours. The test results are shown in Table 1.
[0059] Table 1 Performance test results of the colloids prepared in Examples 1-4 and Comparative Examples 1-6
[0060] It can be seen from the data in Table 1 that the adhesive properties and elongation at break of the sealants prepared in Examples 1-5 are significantly superior to those of the comparative examples, and the sealants are stable in terms of aging resistance and reliable in long-term use. The imine bond on the side chain of the modified polysiloxane has good coordination properties, and its N atoms and O atoms form a relatively strong coordination effect by pairing with the empty d orbital of the Fe atom, so that the sealant can play a good adsorption role on the surface of the steel plate, and form a film on the surface of the steel plate, play a corrosion inhibition role, prevent further corrosion of the metal, and improve the durability of the steel structure.
[0061] Compared with Example 1, the m value of the modified polysiloxane in Comparative Example 1 is too high, the n value of the modified polysiloxane in Comparative Example 2 is too low, the content of imide bonds and metal coordination bonds formed in the colloidal system is low, a dense adsorption film cannot be formed on the steel surface, and the overall durability is poor.
[0062] Compared with Example 2, Comparative Example 3 does not contain a light stabilizer and an antioxidant, and the overall durability is poor.
[0063] Compared with Example 2, the modified polysiloxane molecular chain in Comparative Example 4 is too long, which will reduce the degree of cross-linking of the system, significantly reduce the colloid strength, and deteriorate the sealing performance.
[0064] Compared with Example 3, Comparative Example 5 does not contain an imine bond. Although a certain amount of antioxidant and light stabilizer are added, the material's anti-ultraviolet aging performance is slightly improved, but the colloid has no corrosion inhibition effect on the steel surface. After wet-heat aging, the steel plate surface is severely corroded and the bonding performance is poor.
[0065] Compared with Example 4, the modified polysiloxane side chain alkyl chain in Comparative Example 6 is longer, which has a certain hindering effect on imine coordination, reduces the coordination effect of the colloid on the steel plate surface, weakens the corrosion inhibition effect, and reduces the anti-aging ability, which cannot meet the actual use requirements.
[0066] In summary, within the scope of the formula claimed in the present invention, the performance of the sealant in all aspects can meet the requirements. When the formula exceeds the scope of the present invention, some properties of the sealant will be obviously insufficient.
Claims
1. A high-durability sealant for sealing steel structure plate seams, characterized in that The sealant comprises the following components in parts by weight: 30-50 parts of modified polysiloxane, 1-6 parts of silane oligomer, 30-60 parts of inorganic filler, 0.1-1 parts of thixotropic agent, 0.01-0.2 parts of catalyst, 30-60 parts of crosslinking agent, 0.3-2 parts of silane coupling agent, 0.1-0.5 parts of light stabilizer and 0.1-1 parts of antioxidant.
2. The high-durability sealant for sealing steel structure plate seams according to claim 1, characterized in that The modified polysiloxane has the following general formula: In the formula, R is any one of methyl, ethyl, n-propyl, and isopropyl; 10≤m≤100, 20≤n≤100, m and n are both positive numbers.
3. The high-durability sealant for sealing steel structure plate seams according to claim 1, characterized in that: The preparation method of the modified polysiloxane comprises the following steps: dissolving the pendant aminopropyl polysiloxane and the corresponding mass of furfural in tetrahydrofuran (THF), controlling the molar ratio of the amino group to the aldehyde group at 1:1, adding anhydrous sodium sulfate (Na2SO4), stirring the mixture at room temperature for 24 hours, removing Na2SO4 by centrifugation, removing the solvent by rotary evaporation, and drying in an oven under vacuum for 12 hours to obtain the modified polysiloxane.
4. The high-durability sealant for sealing steel structure plate seams according to claim 1, characterized in that The number average molecular weight of the modified polysiloxane is 6000-20000.
5. The high-durability sealant for sealing steel structure plate seams according to claim 1, characterized in that The inorganic filler includes at least one of calcium carbonate and silicon powder. Further, the calcium carbonate is preferably at least one of heavy calcium carbonate and nano calcium carbonate.
6. The plate seam sealant for steel structure according to claim 1, characterized in that The catalyst is composed of one or more of dioctyltin diacetate, dioctyltin dilaurate, dioctyltin dioctoate, dibutyltin diacetate, dibutyltin dilaurate, dibutyltin dioctoate, isopropyl titanate, isobutyl titanate, and n-butyl titanate; the crosslinking agent is composed of one or more of methyltriacetoxysilane, ethyltriacetoxysilane, vinyltriacetoxysilane, tetraethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, or vinyltriethoxysilane.
7. The high-durability sealant for sealing steel structure plate seams according to claim 1, characterized in that The light stabilizer is composed of one or more compounds such as benzotriazole ultraviolet light absorbers and hindered amine ultraviolet light stabilizers.
8. The high-durability sealant for sealing steel structure plate seams according to claim 1, characterized in that The silane coupling agent is composed of one or more of 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane or N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane.
9. A high-durability sealant for sealing steel structure plate seams according to claims 1-8, characterized in that The sealant can improve the corrosion resistance of the steel surface and improve the overall durability.
10. Use of the high-durability sealant for sealing steel structure plate seams according to any one of claims 1 to 9 in sealing steel structure plate seams.
Citation Information
Patent Citations
Two-component organic silicon sealant and preparation method thereof
CN114621724A
Underwater-curable organosilicon sealant as well as preparation method and application thereof
CN116445127A
Organosilicon sealant and preparation method thereof
CN117801782A
Flame-retardant heat-conducting epoxy resin compound and preparation method thereof
CN117757218A
Bis-Schiff-base thermosetting elastomers
US10662329B1